Nb2O5 as a radical modulator during oxidative dehydrogenation and as a Lewis acid promoter in CO2 assisted dehydrogenation of octane over confined 2D engineered NiO–Nb2O5–Al2O3. Issue 15 (8th July 2021) - Farahani, Majid D.; Fadlalla, Mohamed I.; Ezekiel, Itegbeyogene P.; Osman, Nadir S. E.; Moyo, Thomas; Claeys, Michael; Friedrich, Holger B.
Abstract : Ordered mesoporous 2D NiO–Nb2 O5 –Al2 O3 nano-composites were used for CO2 assisted dehydrogenation of n -octane; and the close proximity of Ni and Nb2 O5 in the optimised catalyst promoted CO2 dissociation and substantially prolonged alkane activation. Abstract : Mesoporous 2D NiO–Nb2 O5 –Al2 O3 nanorods (and, for the first time, template free ordered mesoporous alumina (OMA)) were prepared via glycol-thermal synthesis for the direct transformation of octane to octenes via CO2 assisted dehydrogenation (CO2 -DH). Nb2 O5 addition modified the confinement effect and metal support interaction between NiO and alumina. The catalyst with an optimal confinement effect between all metal oxides in the nanorod composite provided 6% steady state n -octane conversion with ∼80% selectivity to C8 aromatics and olefins. Characterisation data of the fresh and used catalysts, obtained from CO2 -DH as well as reverse water gas shift (RWGS) reactions, was used to identify the possible mechanism over this catalyst. Nb2 O5 addition to the NiO catalyst facilitates CO2 -DH by promoting RWGS and reverse-Boudouard reactions by forming O* from CO2 dissociation. Also, application of these materials for the oxidative dehydrogenation of n -octane and propane using air revealed the contribution of a radical mechanism.